The Prince of Ireland and the three magic stallions - Milligan, Bryce, 1953- (Holiday House, 2003)
In this retelling of an Irish folktale, the Prince of Ireland's stepmother curses him to stay no longer than two nights anywhere until he brings her a giant's horses from the western edge of the world.